Clinical effects of laparoscopic surgery for the treatment of endometriosis and endometriosis-fertility: A retrospective study of 226 cases - Li, Haiyan; Han, Yingxue; Cai, Yuru; Su, Xiaojuan; Tan, Lixia (Frontiers in Surgery, 2023)
Introduction To determine the clinical effects of laparoscopic surgery (LS) in the treatment of endometriosis and endometriosis-fertility. Methods Two hundred twenty-six patients with endometriosis who underwent LS (LS group, n = 176) or laparotomy (LT group, n = 50) at the Third Hospital of Shijiazhuang City from June 2011 to June 2013 were included in this study, and their clinical outcomes for endometriosis and infertility were compared. All patients were followed up for 1 year after surgery to determine postoperative pregnancies in patients with endometriosis. Results The operative times between the LS and LT groups were not significantly different (P > 0.05); however, the length of stay in the hospital and blood loss in the LS group were significantly different from the LT group (P < 0.05). The incidence of postoperative symptoms were lower in the LS group than the LT group (P < 0.05). The postoperative pregnancy rates in the two groups were significantly different, including the infertility patients (P < 0.05). Conclusions Compared with LT, LS significantly reduced pain and improved the quality of life in women with endometriosis. These results can provide a reference for the clinical treatment of endometriosis.